1990
DOI: 10.3758/bf03207084
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among auditory dimensions: Timbre, pitch, and loudness

Abstract: In two experiments, we examined whether or not pairs of auditory dimensions-timbre-loudness (Experiment 1) and timbre-pitch (Experiment 2)-interact in speeded classification. Subjects classified values from one dimension while the other dimension was (1) held constant (baseline), (2) varied orthogonally (filtering), or (3) correlated linearly. The subjects showed substantial Garner interference when classifying all dimensions-that is, poor performance at filtering relative to baseline. Timbre and loudness disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
198
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(229 citation statements)
references
References 36 publications
27
198
1
Order By: Relevance
“…Some researchers have found that the timbre of a tone affects its perceived pitch (e.g., Krumhansl & Iverson, 1992, Experiment 1; Melara & Marks, 1990a, 1990b, 1990cPlatt & Racine, 1985;Singh & Hirsh, 1992;Wapnick & Freeman, 1980), whereas others have found no effect of timbre on pitch perception (e.g., Krumhansl & Iverson, 1992, Experiments 2 and 3; Semal & Demany 1991, 1993. It seems that those studies presenting tones in the absence of other tones tend to find an interaction between pitch and timbre, whereas studies presenting tones within the context of other tones find no such interaction (but see also , in which pitch and timbre difference thresholds for isolated tones were not affected by variation in the irrelevant dimension).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have found that the timbre of a tone affects its perceived pitch (e.g., Krumhansl & Iverson, 1992, Experiment 1; Melara & Marks, 1990a, 1990b, 1990cPlatt & Racine, 1985;Singh & Hirsh, 1992;Wapnick & Freeman, 1980), whereas others have found no effect of timbre on pitch perception (e.g., Krumhansl & Iverson, 1992, Experiments 2 and 3; Semal & Demany 1991, 1993. It seems that those studies presenting tones in the absence of other tones tend to find an interaction between pitch and timbre, whereas studies presenting tones within the context of other tones find no such interaction (but see also , in which pitch and timbre difference thresholds for isolated tones were not affected by variation in the irrelevant dimension).…”
mentioning
confidence: 99%
“…Correspondence concerning this article should be addressed to C. M. Warrier, Communication Sciences and Disorders, Francis Searle Building,Northwestern University, Evanston, IL 60208 (e-mail: cwarrier@northwestern.edu). & Marks, 1990a& Marks, , 1990b& Marks, , 1990c. Melara and Marks performed a series of experiments in which pitch, timbre, and loudness interactions were investigated, using the Garner (1974) speeded classification method; they observed how redundant and interfering information from the unattended dimensionaffected reactiontimes, and looked at classification reaction times for selective and divided attention to these dimensions with varying orientations of stimulus axes.…”
mentioning
confidence: 99%
“…Moreover, as shown in Experiments 3 and 6, this asymmetry is maintained in the face of indirect reference to the stimulus, as when an auditory label signals a visual stimulus. Finally, as shown in Experiments 1-3, the interaction between past and present position appears to have a postperceptual origin, as indicated by the recurrence of the pattern that Melara and Marks (1990a, 1990b, 1990d call semantic crosstalk. This set of results suggests the following conclusion: .Processing systems tie attributes to stimuli and, in so doing, tie the present to the past.…”
Section: Discussionmentioning
confidence: 99%
“…One may note in Table 5 that subjects' classifications were much faster in this experiment than in previous ones, but these speeds are not atypical for perceptual judgments, even between interacting dimensions (cf. Melara & Marks, 1990a, 1990b, 1990d.…”
Section: Methodsmentioning
confidence: 99%
“…Although concepts of integrality and separability have traditionally been reserved for visual dimensions (Kemler Nelson, 1993;Maddox, 1992), there are a number of studies that have reported the status of dimensional interaction within the auditory domain for a variety of sound dimensions, including pitch, harmonicity, timbre, location, loudness, and vocal quality (e.g., Caclin, Giard, Smith, & McAdams, 2007;Caclin et al, 2008;Dyson & Alain, 2008;Dyson & Quinlan, 2004;Grau & Kemler Nelson, 1988;Harris, Pikler, Hoffman, & Ehmer, 1958;Krumhansl & Iverson, 1992;Melara & Marks, 1990;Mondor, Zatorre, & Terrio, 1998;Patching & Quinlan, 2002;Wood, 1975). The present aim was not to provide evidence that the nature of an interaction between any pair of auditory dimensions is one or the other but, rather, to detail how dimensional relations estimated at the macrolevel relate to estimates derived at the microlevel.…”
Section: Experime R R Ntmentioning
confidence: 99%